The flight attendant [compact disc, unabridged] : a novel - Bohjalian, Chris, 1962- (Random House Audio, 2018)
When binge-drinking flight attendant Cassandra wakes up in a Dubai hotel next to a body, she has no idea what happened, and all she can think to do is lie about it. She lies to her coworkers, and eventually to the FBI agents who question her. Could she have killed him? If not, then who did?